Experiential Gains with a New Technology: An Empirical Investigation of Hydraulic Fracturing. (August 2015) - Fitzgerald, Timothy
Abstract : In conjunction with technologies such as horizontal drilling, hydraulic fracturing has transformed U.S. and world energy outlooks by adding reserves from unconventional resources. Fracturing was developed by experimentation and experience. This study empirically analyzes fracturing data for wells in the Williston Basin in North Dakota and Montana, focusing on firms' ability to improve well production over time through collaboration. Results suggest that producers gain from experience with fracturing and that proprietary additives are not generally correlated with greater production but have value for some firms. Experiential gains are stronger for operators than for contractors, but some operator-contractor pairings have productive value.